(Re)defining entrepreneurship in a post-pandemic context - Dias, Á.; Patuleia, M. (Social Sciences, 2023)
More than three years have passed since the first lockdown, and the world is not the same. The new context that emerged from the pandemic is now influenced by conflicts, inflation, social conflicts, and the omnipresent issue of global warming. All these (and more) led consumers, companies, and governments to rethink their behavior. Several studies have focused on the behavior of these stakeholders in the post-pandemic context; however, studies focused on the development of entrepreneurial skills in a post-pandemic context have been scarce. At the same time, there is a growing number of voices calling for the need to adopt business models based on a circular economy (Dias et al. 2022). Again, at this level, research exploring the link between entrepreneurship and the development of business models for a circular economy is limited.